Einstein$1 (Bs Struggles with Quantum Theorys A Reappraisal - Home, Dipankar; Whitaker, Andrew; SpringerLink (Online service) (New York, NY : Springer New York, 2007)
Einstein$1 (Bs Struggles with Quantum Theory: A Reappraisal by Dipankar Home and Andrew Whitaker provides a detailed account of Albert Einstein$1 (Bs thinking in regard to quantum physics. Until recently, most of Einstein$1 (Bs views on quantum physics were dismissed and even ridiculed; some critics even suggested that Einstein was not able to grasp the complexities of the formalism of quantum theory and subtleties of the standard interpretation of this theory known as the Copenhagen interpretation put forward by Niels Bohr and his colleagues. But was that true? Modern scholarship argues otherwise, insist Drs. Home and Whitaker, who painstakingly explain the questions Einstein raised as well as offer a detailed discussion of Einstein$1 (Bs position and major contributions to quantum theory, connecting them with contemporary studies on fundamental aspects of this theory. This unique book presents a mathematical as well as a non-mathematical route through the theories, controversies, and investigations, making the discourse both readable and understandable to anyone interested in Einstein and quantum theory. The authors also examine recent developments in quantum theory and reveal the influence Einstein has had, and will continue to have, in this important field. Sir Roger Penrose writes in his Forward: "It is immensely refreshing...to find a book which at last pays due respect to the later views of Einstein...Dipankar Home and Andrew Whitaker have provided us with masterly expositions on the issues....This book is likely to retain a very significant role for such developments [in quantum theory] for many decades to come.".s
A Setting the Scene -- The Philosophical Background Einstein and Mach -- Einstein and Quantum Theory: The Early Years -- Quantum Mechanics and its Fundamental Issues -- The Standard Interpretation of Quantum Mechanics -- B Einstein Confronting Quantum Theory from 1925 -- Einstein$1 (Bs Approaches to Quantum Theory 1925-1935 -- EPR and its Aftermath -- Einstein and the Macroscopic Limit of Quantum Mechanics -- Summary of Einstein$1 (Bs Views -- C Denouement -- Bell$1 (Bs Contributions and Quantum Non-locality -- Non-standard Quantum Interpretations -- Einstein and Quantum Information Theory -- Bridging the Quantum-Classical Divide -- D Looking Forward -- Quantum Foundations: General Outlook -- Assessment of Einstein$1 (Bs Views and Contributions.s
Keywords: Physics; History; Quantum physics; Quantum computers; Spintronics; Physics; Quantum Physics; History of Science; History and Philosophical Foundations of Physics; Quantum Information Technology, Spintronics; Electronic books